AL-QUR’AN AND HUMAN MIND: THE FACTS OF SCIENCE DEVELOPMENT - Prima Aswirna; Reza Fahmi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
The scientific facts claimed in the Qur'an are found in different discorces, including in the terms of creation, astronomy, human reproduction, oceanology, embroyology, zoology, and water cycle. This article explored the miracle of al-Qur’an on scientific knowledge, especially natural science. Applying the approach of descriptive analysis, this study was able to demonstrate the empirical facts about the miracle of al-Qur’an that have been discovered the scientific truth in science. This article also showed the limitations of human intellect to understand all the realities existing in this world, as well as advocated human beings on the importance of returning dialoging al-Qur'an and intellect in exploring science.